2022
DOI: 10.13075/ijomeh.1896.01912
|View full text |Cite
|
Sign up to set email alerts
|

The role of well-known antioxidant vitamins in the prevention of cadmium-induced toxicity

Abstract: Long-term exposure to cadmium (Cd) leads to the development of a number of conditions associated with liver and kidney damage, reproductive and cardiovascular disorders, in addition to visual impairment, blindness and hearing loss, among others. Cadmium has been classified as a human carcinogen by the International Agency for Research on Cancer. The toxicity of Cd is related to its pro-oxidant properties and the associated increase in oxidative stress. Antioxidant ingredients may be helpful in preventing the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Increasing evidence suggests that vitamin, nutraceutical supplementation may play an important role in women ‘s health [ 47 , 48 ]. Indeed, it has long been shown that vitamins E, C and A and β-carotene are effective in reducing Cd concentrations in organs and tissues and reducing Cd-induced toxic effects, including reproductive toxicity [ 49 ]. In addition, Cd-induced gonadal injury in male rats has also been reported to be relieved by supplementation with nutrients such as vitamins and carotenoids [ 50 – 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that vitamin, nutraceutical supplementation may play an important role in women ‘s health [ 47 , 48 ]. Indeed, it has long been shown that vitamins E, C and A and β-carotene are effective in reducing Cd concentrations in organs and tissues and reducing Cd-induced toxic effects, including reproductive toxicity [ 49 ]. In addition, Cd-induced gonadal injury in male rats has also been reported to be relieved by supplementation with nutrients such as vitamins and carotenoids [ 50 – 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention and treatment methods depend on cadmium chelating agents, such as Ca-EDTA [268], meso-2,3-dimercaptosuccinic acid (DMSA), and its lipophilic alkyl monoester MiADMSA [269,270]. Moreover, antioxidant vitamins A, C, and E, as well as selenium, zinc, and magnesium supplementation, have been proven to detoxify cadmium [271].…”
Section: Health Implications Of Impaired Functioning Of Cadmium Trans...mentioning
confidence: 99%
“…In addition, several studies in animal models showed that vitamins A, C, E are able to decrease the toxic effects of Cd in the kidney, liver, spleen, blood, bones, and brain. However, further human studies are needed to clarify the role of these antioxidant vitamins in reducing Cd-induced toxicity [118].…”
Section: Detoxifying Agents and Chelating Agents For The Prevention A...mentioning
confidence: 99%